2020
DOI: 10.3390/resources9110131
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Valuable and Critical Elements Recovery Potential in Ashes from Processes of Solid Municipal Waste and Sewage Sludge Thermal Treatment

Abstract: Due to the increasing amount of produced and accumulated wastes, a potential source of elements might be the global waste stream coming from the waste incineration process. As a result of this process, bottom ash, fly ash and air pollution control residues are produced. The goal of this study was to evaluate the raw material potential of the anthropogenic materials which are fly ashes from municipal waste incineration and municipal sewage sludge incineration, and the possibility for the recovery of metallic or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…In the first stage, particulates, which are the fine mineral fraction of sewage sludge and sand from the fluidised bed, are removed from flue gases using multicyclones and an electrostatic precipitator. They consist mainly of SiO 2 , P 2 O 5 , CaO, Al 2 O 3 and MgO, which is confirmed by the results of studies reported by Cyr et al and Kasina et al [18,31]. According to the authors, ISSA mostly contains P 2 O 5 contents from 10% to 26%; in the studied FA ash, this value was 26.4%.…”
Section: Chemical Compositionsupporting
confidence: 79%
“…In the first stage, particulates, which are the fine mineral fraction of sewage sludge and sand from the fluidised bed, are removed from flue gases using multicyclones and an electrostatic precipitator. They consist mainly of SiO 2 , P 2 O 5 , CaO, Al 2 O 3 and MgO, which is confirmed by the results of studies reported by Cyr et al and Kasina et al [18,31]. According to the authors, ISSA mostly contains P 2 O 5 contents from 10% to 26%; in the studied FA ash, this value was 26.4%.…”
Section: Chemical Compositionsupporting
confidence: 79%
“…It is, thus, important to evaluate the bioavailability of phosphorus recovered from waste and its possible usage in the fertilizer production. The studied ISSA fulfilled requirements for non-hazardous waste (Kasina et al 2021) and usage as solid mineral fertilizers are fulfilled following national and EU norms (Kasina et al 2020) due to high content of macronutrients (K 2 O + P 2 O 5 ) and acceptable content of potentially toxic elements (As, Pb, Cd, Hg).…”
Section: Results Of Sequential Extraction -The Influence Of the Resul...mentioning
confidence: 99%
“…The phosphorus present in the ISSA starting samples varied between 7 and 8%. These relatively high concentrations enable the comparison of ISSA to medium grade phosphorus ores (Kasina et al 2020 ). The phosphorus in ISSA is usually present not as a free phosphate but combined aggregates or phases (Franz 2008 ); therefore, its identification is relevant.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the composition of MSW-FA is greatly dependent on the MSW sources [50,51] and the type of incinerators [52]. O), calcite (CaCO 3 ), sylvite (KCl), and lime (CaO) [53][54][55][56][57].…”
Section: Msw-fa As Source To Silicate and Alumina In Zeolite Synthesismentioning
confidence: 99%